An Adjunction-Based Approach to Non-Standard Variation (“el microalga”, “un alita”) - Bárbara Marqueta Gracia (Catalan Journal of Linguistics, 2025)
In Spanish, feminine singular nouns beginning with a stressed /a/, such as arma ‘weapon’ and asa ‘handle’, do not take the standard article forms la and una, but el and un. This paper examines the non-standard uses of el and un observed in morphologically complex words, such as prefixed nouns (el microalga) and diminutives (un alita). The hypothesis is that what makes these variants possible is the adjunct status of prefixes and diminutive suffixes. It is claimed that adjuncts do not obligatorily trigger the reassignment of standard forms la and una, like a head would, because they can be late-merged.